Electrospun 3D composite nano-flowers for high performance triple-cation perovskite solar cells - Mahmud, Md Arafat; Elumalai, Naveen Kumar; Pal, Bhupendar; Rajan, Jose; Upama, Mushfika Baishakhi; Wang, Dian; Goncales, Vinicius R.; Xu, Cheng; Haque, Faiazul; Uddin, Ashraf (Elsevier, 2018)
Three dimensional (3-D) flower-shaped SnO2-TiO2 nano-structure has been synthesized by electrospinning and incorporated on top of sol-gel ZnO ETL to fabricate highly efficient (highest efficiency: 17.25%) triple-cation (methyl ammonium, formamidinium and rubidium cations) based perovskite solar cell (PSC). The flower-based PSCs demonstrate superior photovoltaic performance compared to control ZnO or one-dimensional (1-D) fiber-shaped nano-structure ETL based devices. Nano-structured ETLs passivate the interstitial trap sites in pristine ZnO by intercalation of metal atoms in host ZnO lattice matrix and increase the n-type conductivity of the (nano-structured) ETL films by reducing the functional groups on ZnO surface. The accumulated ions at the perovskite/ETL interface are also welldistributed and hence the accumulation capacitance is significantly reduced in nano-structured ETL based PSCs, due to the branch-structured ETL network. Moreover, the nano-flower based PSC demonstrates superior charge transfer property, compared to nano-fiber based PSC owing to enhanced material crystallinity and higher effective surface area of 3-D nano-flower network, with respect to 1-D nano-fiber structure. The photo-current hysteretic phenomena are also most suppressed in nano-flower based PSC, due to mitigated electrode polarization mechanism in it. Adding to the merits, PSCs incorporating nanoflower ETL demonstrate enhanced device stability compared to the control devices, retaining about 92% of its initial efficiency even after a month. The enhanced device stability with nano-flower based PSC is contributed by the lower hydrophilicity, lower extent of functional surface hydroxyl group and lower content of vacant interstitial trap sites of the respective ETL film.